2013
DOI: 10.1021/nl400896c
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanocrystal Array/Silicon Nanoantennas as Wavelength-Selective Photoswitches

Abstract: Au nanocrystal array/silicon nanoantennas exhibiting wavelength-selective photocurrent enhancement were successfully fabricated by a facile and inexpensive method combining colloidal lithography (CL) and a metal-assisted chemical etching (MaCE) process. The localized surface plasmon resonance (LSPR) response and wavelength-selective photocurrent enhancement characteristics were achieved by tuning the depth of immersion of Au nanocrystal arrays in silicon through a MaCE process. The wavelength selectivity of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The half-pitch resolution of the proposed SPILM can be further improved by increasing the refractive index of the PR and reducing the thickness of the PR. The proposed SPILM has the potential for fabricating large-area periodic nanostructures, which were widely used in fields such as electromagnetic polarization manipulation242526, strong-field emission3637, wavelength-selective photocurrent enhancement38 and surface-enhanced Raman scattering39. Our findings open up an avenue to push the half-pitch resolution of photolithography towards 10 nm.…”
Section: Resultsmentioning
confidence: 82%
“…The half-pitch resolution of the proposed SPILM can be further improved by increasing the refractive index of the PR and reducing the thickness of the PR. The proposed SPILM has the potential for fabricating large-area periodic nanostructures, which were widely used in fields such as electromagnetic polarization manipulation242526, strong-field emission3637, wavelength-selective photocurrent enhancement38 and surface-enhanced Raman scattering39. Our findings open up an avenue to push the half-pitch resolution of photolithography towards 10 nm.…”
Section: Resultsmentioning
confidence: 82%
“…However, the observed photocatalytic activity of the ZNA–35AuNPs is slightly better than that of the ZNA–10AuNPs at low particle loading (0–1.2 at%), as shown in Figure b. It is reported that the enhancement of optical absorption results from high near‐field intensities induced by the localized SPR response of metallic nanostructures is proportional to the electromagnetic field intensities . A high local electromagnetic field leads to increased light absorption and effective generation of energetic hot electron‐hole pairs.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, surface plasmon resonance (SPR), defined as the collective oscillations of free electrons in plasmonic nanoparticles (especially Au) induced by visible light illumination, can enlarge the localized electric field in the proximity of the metal particles; at the same time, the interaction of the localized electric field with the neighboring semiconductor generates additional electron‐hole pairs in the near‐surface region of the semiconductor . Most recently, the plasmonic effect has often been considered as the cause of visible photoactivity …”
Section: Introductionmentioning
confidence: 99%
“…Semiconductors incorporating metal nanostructures are particularly fascinating because of their ability to improve the performance of such devices. Surface plasmon resonance (SPR) is generated from metal nanoparticles (NPs) when the incident light is coupled with the oscillation of free electrons; this phenomenon, which scatters more light and amplifies the electromagnetic field, can lead to the distinctive properties of plasmonic nanolasers [5,6] and photoswitches [7,8], or to the enhanced performance of solar cells [9][10][11], water splitting systems [12], and photocatalysts [13,14]. In general, three factors can improve the performance of an optoelectronic device after incorporating plasmonic metal nanostructures: subwavelength scattering of metallic structures; coupling of the near-field localized surface plasmon (LSP) of the metal NPs and the absorber materials; and the generation of surface plasmon polaritons from the metal grating at the metal-semiconductor interface [15].…”
Section: Introductionmentioning
confidence: 99%